Enhanced stability in perovskite solar cells via room-temperature processing. Issue 41 (8th October 2021) - Wang, Boxin; Bi, Shiqing; Zhou, Jiyu; Ahmad, Nafees; Zhang, Dongyang; Zhang, Yuan; Zhou, Huiqiong
Abstract : Stable and efficient perovskite solar cells were prepared via room-temperature processing, which eliminated ion evaporation. Abstract : Perovskite solar cells (PSC) have undergone rapid development in recent years due to their excellent photovoltaic performance. To attain desirable crystallization in perovskites, thermal annealing is widely adopted, although this does simultaneously introduce unfavourable degradation channels via the formation of defects. Here, we propose an illumination-assisted room-temperature process to replace traditional thermal annealing. We show that, using this strategy, similar power conversion efficiencies to those obtained with thermal annealing were obtained. Avoiding the negative effects that are induced by thermal treatment of the materials, the room-temperature-processed devices exhibit an impressive shelf stability, with no obvious degradation after 166 days. The results demonstrated in this work provide the opportunity to achieve room-temperature-annealed PSCs without compromising their stability toward the realistic application of PSC-based photovoltaic techniques.